Examining the mediating effect of attitude towards electronic Words-of Mouth (eWOM) on the relation between the trust in eWOM source and intention to follow eWOM among Malaysian travellers - Nur Thara Atikah Zainal; Amran Harun; Lily Jaratin (Elsevier, 2017)
This study aims to investigate the influence of trusting electronic word-of-mouth (eWOM) sources available online and attitude on intention to follow eWOM among travellers in Malaysia. A total of 280 questionnaires were collected from respondents via an online survey. The findings indicate that trust in the honesty, competence and benevolence of eWOM sources has a significant impact on attitude towards eWOM as well as the intention to follow it. However, the results also indicate that attitude partially mediates the relationship between trust in eWOM source and intention to follow it. The findings of this study can have significant implications for the tourism industry.